The Dorn gold deposit in northern Victoria Land, Antarctica: Structure, hydrothermal alteration, and implications for the Gondwana Pacific margin - CRISPINI, LAURA; FEDERICO, LAURA; CAPPONI, GIOVANNI; TALARICO, FRANCO MARIA (Gondwana Research, 2011)
The Dorn gold deposit in northern Victoria Land, Antarctica is a fault related gold-only deposit and it represents the first described occurrence of gold mineralization in Paleozoic terranes of the Antarctic continent. The deposit is hosted in lower greenschist facies Middle Cambrian metavolcanic and metasedimentary rocks of the Bowers terrane. Gold-bearing veins are located in a brittle-ductile reverse high-strain zone, which was produced by transpressional deformation that overprints the structures of the Cambrian-Ordovician Ross Orogeny. The vein system is surrounded by a hydrothermal alteration zone that is as much as 300-m-wide, where the host rocks are partially to completely transformed into Fe-Mg carbonate-rich rocks with different degrees of replacement of the original mineralogy and texture. The type of host rock, the temperature estimates for mineralization from 290-320 degrees C, the quartz dominant vein system with sulfides and Fe-rich carbonates, and the controlling structures linked to a convergent margin tectonic setting together suggest that this mineralized vein system can be classified as an orogenic gold deposit. Close analogies are found with deposits of the Stawell zone in western Victoria, which is consistent with the correlation between units and hydrothermal events in northern Victoria land and southeastern Australia. (C) 2010 International Association for Gondwana Research. Published by Elsevier B.V. All rights reserved.